Multiple Recurrences and Late Metastasis of Adamantinoma in the Tibia: A Case Report. (December 2014) - Giannoulis, DK; Gantsos, A; Giotis, D; Paschos, NK; Vagionas, A; Arnaoutoglou, CM; Pentheroudakis, G; Xenakis, TA
Adamantinoma is a rare, low-grade, malignant bone tumour. We report on a 46-year-old woman who had early multiple recurrences of adamantinoma of the right tibia and late metastasis to the lung and ribs 13 years after the first surgical treatment. She underwent multiple complete tumour excisions and eventually below-knee amputation and removal of the left lung and sixth to eighth ribs.